SEKO ALAS MLEBU GELAS: Pelatihan Bagi Petani Kopi di Tegalsari Purwosari Perbukitan Menoreh - Moh Soehadha (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2023)
Coffee is a potential commodity in Tegalsari, Menoreh Hills, Kulonprogo. Despite the potential for development, proper "black gold" cultivation activities; such as red picking, post-harvest handling, roasting, marketing and brewing methods have not yet become a culture among coffee farmers. Therefore, empowerment of coffee farmers through training is important. The research method and empowerment strategy were carried out using Participatory Action Research (PAR) procedures. The strategy of empowering coffee farmers was carried out through a process of adaptive, collaborative, and interactive with coffee farmers and enthusiasts as well as the local community of Menoreh. The three strategies are used to find a meeting point between the socio-cultural system of the coffee farming community and the coffee-loving community as stakeholders. The results of the analysis of the living conditions of coffee farmers in Tegalsari showed that the main problem for farmers to develop the coffee business is knowledge and technology. Based on these conditions, training was conducted for coffee farmers with materials; cultivation, post-harvest and brewing. The results of the training showed that the farmers were generally enthusiastic in participating in the training. There was an increase in knowledge based on the pre-test and post-test results. The key to increasing the income of coffee farmers is when they can unite the upstream activities of cultivation and post-harvest with the downstream activities of processing, roasting and brewing or in the expression bringing coffee "seko alas mlebu gelas" (from the field in the forest to the glass).